Rekonstruksi Peran Dan Fungsi Masjid Sebagai Ruang Publik: Studi Kasus Di Masjid Namira Lamongan - Umah, Khurul Aimmatul; Avif Alfiyah (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2023)
The reality that there is a society has undergone a change and so the masjid has also experienced its development, both in terms of buildings and functions. Inevitably entering the millennium there is a new problem which is the effect of rapid social change, namely the narrowing of the function of the masjid. Therefore, in this case, it acts as a human life guide, namely religion, which must carry out its function as a controlling agent of social change that has an impact on social life. This study aims to find out how the dynamics of the development of Namira Masjid are reviewed from the manager's perspective in optimizing the function and role of the masjid. The researcher used a qualitative research method with a phenomenology approach with the technique of collecting data through observation and interviews. Qualitative research was chosen as the type of research in this study because it was judged to be used to reveal and understand the social phenomena that exist in society. The role of Namira masjid as an optimal public space is directed at strengthening-strengthening in several aspects that must be a priority, namely: First, optimizing the function of the Hissiyah (building) masjid. Second, optimizing the function of the masjid in the aspect of meaning (purpose). Third, optimizing the function of the masjid in the aspects of ijtima’iyah (all activities). Because the essence of the function of the masjid is not only as a place of prayer alone, the masjid is the center of all activities both for worship that have vertical encounters (hablun minallah) and horizontal worship services (hablun minannas)